Drought characteristics projections based on CMIP6 climate change scenarios in Syria - Shifa Mathbout; Javier Martin-Vide; Joan Albert Lopez Bustins (Journal of Hydrology: Regional Studies, 2023)
Study region: Syria Study focus: This study delves into predicting drought characteristics in Syria, focusing on their duration, frequency, and intensity. It utilizes a set of 13 models sourced from the latest CMIP6 dataset, encompassing two distinct SSP scenarios. To evaluate how well CMIP6 represents drought attributes in Syria, the research conducts a comparison with observed monthly climate data from CRU TS v4.06 and ERA 5, as well as the CMIP6 model ensemble outputs for the reference period (1970–2000). New hydrological insights for the region: This study provides new hydrological insights for Syria. It reveals robust projections of increasing drought severity, frequency, and duration, particularly in the north and northeast arid and semi-arid regions, even under aggressive climate mitigation scenarios. Additionally, the study highlights that higher emissions scenarios are associated with more prolonged and intense drought events, potentially impacting even less vulnerable areas. These findings emphasize the urgent need for drought adaptation and mitigation measures, as well as improved water resource planning, in order to address the changing hydrological landscape of the region. Furthermore, it underscores the long-lasting effects of drought on ecosystem recovery, which may span several decades.